2022
DOI: 10.1038/s41598-022-14354-z
|View full text |Cite
|
Sign up to set email alerts
|

Antenna movements as a function of odorants’ biological value in honeybees (Apis mellifera L.)

Abstract: In honeybees, the antennae are highly mobile sensory organs that express scanning movements in various behavioral contexts and toward many stimuli, especially odorants. The rules underlying these movements are still unclear. Using a motion-capture system, we analyzed bees’ antennal responses to a panel of pheromonal and other biologically relevant odorants. We observed clear differences in bees’ antennal responses, with opposite movements to stimuli related to opposite contexts: slow backward movements were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Further studies are therefore needed to assess the influence of the incident direction of the odor flux on the capture by an oscillating antenna, and on the way an insect reorients itself in a directional odor flux. Indeed, for bees at least, several contradictory behaviors have been observed, see Cholé et al (2022) [17]. Furthermore, the concentration field in nature presents complex micro-structures containing information on the odor source [28].…”
Section: Limits Of the Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are therefore needed to assess the influence of the incident direction of the odor flux on the capture by an oscillating antenna, and on the way an insect reorients itself in a directional odor flux. Indeed, for bees at least, several contradictory behaviors have been observed, see Cholé et al (2022) [17]. Furthermore, the concentration field in nature presents complex micro-structures containing information on the odor source [28].…”
Section: Limits Of the Papermentioning
confidence: 99%
“…This active sensing behavior is characterized by a vertical scanning movement, orthogonal to the flow direction (figure 1). Very recent studies with bees however show a dependency of antennal movement with odor characteristics [17,18]. Other authors also recently report that antennal movements and orientations might be related with strategies to obtain additional information about the odor source [19].…”
Section: Introductionmentioning
confidence: 98%
“…A previous study reported that ARs to odorants were limited in newly emerged workers and acquired in the adult life (Cholé et al, 2022). Thus, we next compared the AR to the vertical motion stimuli of newly merged (NE) and flying (F) workers to investigate whether ARs to visual stimuli also mature after emergence.…”
Section: Developmental Maturation Of Ar After Emergencementioning
confidence: 97%
“…In previous studies, the movements of insect antennae were measured by manually determining their position and angle for each frame of video or using phototransistors, which register the movement of the antennae (Erber and Kloppenburg, 1995;Erber et al, 1993;Okada and Toh, 2004). Recently, video analysis technologies have advanced, and methods for automatically tracking the movement of body parts of the honey bee have been reported, such as tracking the marked colors at the tip of the antennae or separating the outline of the antennae from the background by image processing (Cholé et al, 2015;Cholé et al, 2022;Roy Khurana and Sane, 2016). In addition, a markerless posture-tracking tool using deep learning, DeepLabCut (Mathis et al, 2018;Nath et al, 2019), has been widely used in various research fields, such as ecology and neuroscience (Mathis and Mathis, 2020), and is becoming recognized as a powerful tool that does not require special devices or expertise, in addition to being noninvasive and robust in analyzing .…”
Section: Introductionmentioning
confidence: 99%
“…Our first aim was to investigate how antennal movement participates in spatial sampling. It has recently been shown that honeybees orient their antennae towards appetitive odour sources and away from aversive ones (Cholé et al (2022); Gascue et al (2022)). Moreover, the analysis demonstrated a general trend of positive correlation between the time the antennae spent focused on an odour target and its valence (Gascue et al (2022)).…”
Section: Exploration-exploitation Trade-offmentioning
confidence: 99%